USSR in World War II - M. Yu. Myagkov (Vestnik MGIMO-Universiteta)
The article offers an overview of modern historical data on the origins, causes of World War II, the decisive role of the USSR in its victorious end, and also records the main results and lessons of World War II.Hitler's Germany was the main cause of World War II. Nazism, racial theory, mixed with far-reaching geopolitical designs, became the combustible mixture that ignited the fire of global conflict. The war with the Soviet Union was planned to be waged with particular cruelty.The preconditions for the outbreak of World War II were the humiliating provisions of the Versailles Peace Treaty for the German people, as well as the attitude of the "Western democracies" to Russia after 1917 and the Soviet Union as an outcast of world development. Great Britain, France, the United States chose for themselves a policy of ignoring Moscow's interests, they were more likely to cooperate with Hitler's Germany than with Soviet Russia. It was the "Munich Agreement" that became the point of no return to the beginning of the Second World War. Under these conditions, for the USSR, its own security and the conclusion of a non-aggression pact with Germany began to come to the fore, defining the "spheres of interests" of the parties in order to limit the advance of German troops towards the Soviet borders in the event of German aggression against Poland. The non-aggression pact gave the USSR just under two years to rebuild the army and consolidate its defensive potential and pushed the Soviet borders hundreds of kilometers westward. The signing of the Pact was preceded by the failure in August 1939 of the negotiations between the military missions of Britain, France and the USSR, although Moscow took the Anglo-French-Soviet negotiations with all seriousness.The huge losses of the USSR in the summer of 1941 are explained by the following circumstances: before the war, a large-scale modernization of the Red Army was launched, a graduate of a military school did not have sufficient experience in managing an entrusted unit by June 22, 1941; the Red Army was going to bleed the enemy in border battles, stop it with short counterattacks by covering units, carry out defensive operations, and then strike a decisive blow into the depths of the enemy's territory, so the importance of a multi-echeloned long-term defense in 1941 was underestimated by the command of the Red Army and it was not ready for it; significant groupings of the Western Special Military District were drawn into potential salients, which was used by the Germans at the initial stage of the war; Stalin's fear of provoking Hitler to start a war led to slowness in making the most urgent and necessary decisions to bring troops to combat readiness.The Allies delayed the opening of the second front for an unreasonably long time. They, of course, achieved outstanding success in the landing operation in France, however, the enemy's losses in only one Soviet strategic operation in the summer of 1944 ("Bagration") are not inferior, and even exceed, the enemy’s losses on the second front. One of the goals of "Bagration" was to help the Allies.Soviet soldiers liberated Europe at the cost of their lives. At the same time, Moscow could not afford to re-establish a cordon sanitaire around its borders after the war, so that anti- Soviet forces would come to power in the border states. The United States and Great Britain took all measures available to them to quickly remove from the governments of Italy, France and other Western states all the left-wing forces that in 1944-1945 had a serious impact on the politics of their countries.